Effectiveness of Heads of Schools in Supervising Teachers’ Teaching Activities in Secondary Schools in Kagera Region, Tanzania - Mwesiga, Adolphina; Okendo, Evans Ogoti (International Journal of Scientific Research and Management (IJSRM), 2018)
Head of schools are considered imperative in education system for influencing teachers’ teaching commitment to improve school performance and attaining quality education. This necessitated the need of this study to investigate the effectiveness of heads of schools in supervising teachers’ teaching activities in secondary schools in Kagera region. The study was guided by transformational theory. The reviewed literatures indicated the availability of several studies on school leadership and commitment of teachers as factors for school performance. However, still there was a need for investigating the effectiveness of school headship in supervising teachers’ teaching activities in secondary schools as a central variables for effective teaching in secondary schools, due to persisting challenges constrains on leadership effectiveness and education performance. The study employed convergent parallel design from mixed research approach. The target population of the study included all head of schools, academic masters/mistress and teachers in public secondary schools in Kagera region. The sample size comprised 32 schools, 32 head of schools, 32 academic masters/mistress and310 teachers. Probability and non-probability sampling techniques used to sample participants. Instruments for data collection was questionnaires, interview guide and document analysis guide. The study carried out a piloting study into two schools; comprising ten (10) participants. Content validity was established to ensure the validity of instruments, split half method used to ascertain the reliability of questionnaire, dependability and credibility determined the reliability of interview guide. Descriptive statistics used to analyze quantitative data with the use of SPSS version 22 and thematic analysis used for qualitative data analysis. Hypotheses were tested by Pearson Correlation. Results suggest strong significant relationship between school headship and teachers teaching commitment.